Bau von Lehmziegel-Plattformen in der Eisenzeit Der Horizont der Baumeister in Geoktchik Depe und Izat Kuli (Turkmenistan) Kurze Notizen von der Feldarbeit im Gang - Córdoba Zoilo, Joaquín María (ISIMU, 2019)
Some cultural features of the Iron Age in Central Asia, generally well accepted, are now being revised or focused in a different way by modern research. The construction techniques used and the possible influences received by the new states are counted among the newly analyzed elements. The Turkmen and Spanish mission in Dahistan brings interesting and novel facts to the question.